2018
DOI: 10.1029/2017ja024900
|View full text |Cite
|
Sign up to set email alerts
|

Multivariable Comprehensive Analysis of Two Great Geomagnetic Storms of 2015

Abstract: During the year 2015 two great geomagnetic storms (Dst < À200 nT) occurred on 17 March and 22 June. These two geomagnetic storms have similarities. They occurred during the same decreasing phase of the sunspot cycle 24. The interplanetary and magnetospheric environments were calm before the beginning of the storms. Both events were due to Coronal Mass Ejections and High-Speed Solar Wind. Variations of the solar wind velocity and the Bz component of the interplanetary magnetic field were also similar. Two key f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
32
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 39 publications
1
32
1
2
Order By: Relevance
“…Fathy et al (2014) studied the D dyn variations by various filter techniques. More recently, Nava et al (2016), Migoya‐Orue et al (2016), Rodríguez‐Zuluaga et al (2016), Zaourar et al (2017), and Kashcheyev et al (2018) explored various geomagnetic storms using different data sets, for example, vertical total electron content (VTEC), column [O/N 2 ] ratio, F2 layer maximum electron density (NmF2), F2 region maximum electron density height (hmF2), and magnetic data. By employing signal analysis, they reported existence of short‐period oscillations (DP2) as well as diurnal and semidiurnal fluctuations ( D dyn ) in the geomagnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Fathy et al (2014) studied the D dyn variations by various filter techniques. More recently, Nava et al (2016), Migoya‐Orue et al (2016), Rodríguez‐Zuluaga et al (2016), Zaourar et al (2017), and Kashcheyev et al (2018) explored various geomagnetic storms using different data sets, for example, vertical total electron content (VTEC), column [O/N 2 ] ratio, F2 layer maximum electron density (NmF2), F2 region maximum electron density height (hmF2), and magnetic data. By employing signal analysis, they reported existence of short‐period oscillations (DP2) as well as diurnal and semidiurnal fluctuations ( D dyn ) in the geomagnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…The authors have shown that the slow CME plays a main role in the commencement of the geomagnetic storms of the solar cycle 24. Kashcheyev et al (2018) have made a comprehensive analysis on the basis of the two great geomagnetic storms (Dst ≤ −200 nT) which occurred on 17 March and 22 June 2015. It is found that the absence or presence of a scintillation in the African sector is associated with the local time at the beginning of the storm.…”
Section: Introductionmentioning
confidence: 99%
“…The storm effects are analyzed by using the data from the individual GNSS receivers and ground magnetic observatories located in different longitudinal sectors. The approach used in the present study is similar to that used by Nava et al (2016) and Kashcheyev et al (2018). In addition, the storm-time response of the neutral atmosphere in the thermosphere is analyzed by using the global O/N 2 density ratio maps derived from the Global UltraViolet Imager (GUVI) on board the Thermosphere Ionosphere Mesosphere Energetics and Dynamics (TIMED) satellite.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations